Strategic voting in proportional representation systems - Stan Veuger; Tim Ganser (American Enterprise Institute (AEI), 2014)
We propose a model of voter decision-making in proportional representation systems: ultra-rational strategic voters construct expectations of coalitions and policy outcomes based on expected seat distributions and vote to maximize their expected utility from the implemented policy. We examine the predictions of our model using data from the Netherlands and successfully predict the voting behavior of significant numbers of voters. Nevertheless, other factors matter more than our strategic prediction. Three main take-aways follow: (1) At least to some extent, voters seem to take complex coalition considerations into account. (2) There is a need for large-scale quantitative studies about voter decision-making in proportional representation systems. (3) Narrowly defined strategic voting might matter less in proportional representation systems than in plurality systems.
Keywords: A; 330; voting